Aberrant expression of long non‐coding RNA PVT1 in allergic rhinitis children: Correlation with disease risk, symptoms, and Th1/Th2 imbalance. Issue 4 (11th March 2022) - Sun, Yujun; Han, Jingjing; Ma, Haifeng; Ma, Jingbin; Ren, Zengzhi
Abstract: Background: Long non‐coding RNA plasmacytoma variant translocation 1 (lnc‐PVT1) exacerbates inflammation and induces T helper (Th) 1/Th2 imbalance in allergic diseases, but its clinical role in allergic rhinitis (AR) remains unclear. Hence, we conducted this study to compare lnc‐PVT1 expression among AR children, disease controls (DCs), and health controls (HCs), aiming to investigate its clinical application in AR children. Methods: Sixty AR children, 30 DCs, and 30 HCs were enrolled in the study, and then, their lnc‐PVT1 expression in peripheral blood mononuclear cell was detected. Serum interferon‐gamma (IFN‐γ), interleukin 10 (IL‐10), Th1, and Th2 cells in AR children were also analyzed. Besides, lnc‐PVT1 was also detected at Week (W)4 after treatment in AR patients. Results: Lnc‐PVT1 was upregulated in AR children compared with DCs and HCs (both p < 0.001). Lnc‐PVT1 was positively related to nasal rhinorrhea score, itching score, congestion score, and total nasal symptom score (TNSS) in AR children (all p < 0.050), instead of sneezing score ( p = 0.115). Lnc‐PVT1 negatively associated with Th1 cells in AR children ( p = 0.028) also exhibited a negative correlation trend with IFN‐γ (but without statistical significance) ( p = 0.065). Differently, lnc‐PVT1 was positively related to Th2 cells ( p = 0.012) and IL‐10 ( p = 0.021) in AR children. Besides, lnc‐PVT1 and TNSS were reduced at W4 after treatment in AR children (both p < 0.001); notably, lnc‐PVT1 expression decline was correlated with TNSS decline during treatment ( p = 0.013). Conclusion: Lnc‐PVT1 works as a biomarker, whose aberrant expression is related to disease severity, Th1/Th2 imbalance, and its decrement can reflect treatment outcome in AR children. Abstract : The current study enrolled 60 AR children, 30 DCs, and 30 HCs and then detected their lnc‐PVT1 in PBMC. For AR children only, serum IFN‐γ, IL‐10, Th1, and Th2 cells at W0 and lnc‐PVT1 in PBMC at W4 were also analyzed. Interestingly, lnc‐PVT1 was upregulated in AR children compared with DCs and HCs. Lnc‐PVT1 was positively related to nasal rhinorrhea score, itching score, congestion score, and TNSS in AR children. Moreover, lnc‐PVT1 was negatively associated with Th1 cells in AR children and also exhibited a negative correlation trend with IFN‐γ (but without statistical significance). Differently, lnc‐PVT1 was positively related to Th2 cells and IL‐10 in AR children. Besides, lnc‐PVT1 and TNSS were reduced at W4 after treatment in AR children; notably, lnc‐PVT1 decline was correlated with TNSS decline during treatment.